Factors affecting calving to service interval in crossbred Friesian cows in a large dairy farm (Bangladesh Veterinarian, 2022)
To determine the calving to service interval and its associated factors, 125 crossbred Friesian cows were studied. The farm records were randomly examined, and related data were collected on genotype, age, body weight, body condition score (BCS), parity, milk yield, suckling status and season of first postpartum service. The overall calving to service interval in Friesian crossbred cows was 98.9 ± 42.6 days. Calving to service intervals in cows with 50.0%, 62.5 - 68.8% and 75.0 - 87.5% exotic blood were 98.7 ± 41.6, 102.9 ± 58.3 and 94.7 ± 33.6 days, respectively. The calving to service interval in cows aged 42 - 60, 61 - 78 and 79 - 173 months was 74.0 ± 14.4, 108.5 ± 48.9 and 100.8 ± 43.0 days, respectively. The calving to service interval in cows with body weight 140 - 180, 181 - 220 and 221 - 250 Kg was 94.3 ± 38.4, 99.3 ± 41.4 and 134.2 ± 74.9 days, respectively. The calving to service interval in cows with BCS 2.5 - 3.0 and 3.5 - 4.0 was 98.8 ± 42.3 and 99.1 ± 44.3 days, respectively. The calving to service interval in cows with parity 1, 2 - 3 and 4 - 10 was 117.5 ± 76.4, 99.6 ± 40.0 and 96.4 ± 41.2 days, respectively. The calving to service interval in cows with milk yield 0 (dry), 1 - 5, 6 - 10 and 11 - 16 litres was 118.4 ± 51.2, 99.6 ± 45.6, 102.5 ± 45.8 and 84.0 ± 22.1 days, respectively. The calving to service interval in suckling and nonsuckling cows was 100.5 ± 44.3 and 88.8 ± 28.8 days, respectively. The calving to service interval in cows in summer, rainy and winter season was 98.8 ± 41.4, 104.5 ± 46.9 and 95.3 ± 41.9 days, respectively. The difference in calving to service interval among cows of different ages was significant (P